The Usage of Combined Components of Verbal L, Vocal and Visual (3-V Components) of Children in Daily Conversation: Psycholinguistic Observation - Amanda Pratiwi Ismail (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This thesis aims at explaining, describing and a study of research about the pshycholinguistic, in order to know what kind of the usage of combined components of 3-V (Verbal language 7%, Intonation (Vocal) 38%, Body language (Visual) 55% by childrens of age in daily conversation. Research conducted qualitative and quantitative descriptive method research with using triangulation techniques to data collection. There are interview, field research or observation and literature review or document. The results of the study showed that competence and linguistics performance by childrens of age in daily conversation affected by three pshycholinguistic streams, that is behaviouristic pshycholinguistic, cognitive pshycholinguistic and mentalistic pshycholinguistic in improve the delivery of meaning with using combined components of 3-V (Verbal language 7%, Intonation (Visual) 38%, Body language (Visual) 55% in daily conversation. Step and method which is used for improve competence and performance linguistics by childrens of age in daily conversation, that is with how to improve their the affected of three pshycholinguistic streams;  behaviouristic pshycholinguistic, cognitive pshycholinguistic and mentalistic pshycholinguistic is with the childrens needs to learn and study languages through  the pattern as follows: 1. All components, system and language skills are learned in integrated manner. 2. Language learning is done naturally and directly in an authentic context. 3. Language learning is done in stages according to their needs. 4. Language learning is done through trial-error strategic. Skilled at dialogue with interviewing various of the professional of type, the importance of pretend play through sociodramatic play for the affected cognitive pshycholinguistic development by the childrens, behaviouristic pshycholinguistic and their mentalistic pshycholinguistic.